The Effect of The Self-Directed Learning (SDL) Model on The Learning Engagement and Outcomes of Fourth-Grade Students at SDN 1 Mangkung - Muzakkir, Akhmad (Sean Institute, 2025)
This study aimed to determine the effect of the Self-Directed Learning (SDL) model on the learning engagement and outcomes of fourth-grade students in the Indonesian language subject at SDN 1 Mangkung. This study employed a quasi-experimental method with a pretest-posttest control group design. The population consisted of 396 students from SDN 1 Mangkung (N=202) and SDN 2 Mangkung (N=194). A sample of 40 students was selected using cluster random sampling. Data on learning engagement were collected through questionnaires, while learning outcomes were measured using a multiple-choice test. The data were analyzed using an independent samples t-test with SPSS version 22. The results revealed two key findings. First, the learning engagement of students taught with the SDL model was significantly higher than that of students taught with the conventional model. The mean score for the experimental group increased from a pre-test score of 42.65 to a post-test score of 50.05. The t-test analysis yielded a t-value of 5.241, which is greater than the t-table value of 2.024, with a significance of p < 0.05 (Sig. 2-tailed = 0.000). Thus, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted. Second, student learning outcomes also showed a significant improvement in the SDL group, with the mean score increasing from 37.65 to 59.00. The t-test resulted in a t-value of 9.087, exceeding the t-table value of 2.024 (p < 0.05). This indicates that H₀ was rejected and Hₐ was accepted. In conclusion, the SDL model has a significant positive effect on both student engagement and learning outcomes.